Consumer intention to purchase eco-labelled food products in Klang Valley, Malaysia - Najafinejad, Saleh (2013)
The increasing concern among Malaysian consumers on issues such as food safety,environmental protection and animal welfare indicate that nowadays, consumers are not only concerned about the health aspects of food products but they are also very careful on how the products are being produced. Eco is used as a prefix for words related to the environment or ecology. Thus, any product or trade named witheco usually means that the product is produced and processed in an environmentally friendly way. Eco-labeling, which is a voluntary, is an attempt to provide the consumers with relevant information about a product which qualified as having improved environmental performance and efficiency compared to similar products. The objective of this study is to determine the level of Malaysian consumers’ awareness,attitudes, and intention to purchase eco-labeled food products. The survey was conducted in Klang Valley. The Theory of Planned Behaviour (TPB) is applied in this study. The questionnaires, which contains closed ended statements using 7-point Likert scale, were distributed randomly to respondents. The target consumers for this research were consumers who purchase food products from supermarket. Sample size of this study is 1115. The structured questionnaire design consists of three main sections. Characteristics of the respondents are included in the first section. The second section measures the awareness and knowledge of consumers’ towards eco- labeled food products. The third section is designed to measure the attitude, subjective norm and perceived behavioural control that influence the consumer’s green behaviour. Descriptive statistics, chi-square, factor analysis and binary logistic regression were used to analyze the data. The results show that majority of the respondents believe that eco-labelled food products are produced in a sustainable way to protect the environment. It also shows that there are significant differences between the consumer’s awareness towards eco-labeled food products and social demographic profile such as age, geographical area, educational level and income. The result of chi-square test indicates that selected socio-demographic variables such as gender, living area, marital status, educational level, income and age have a significant relationship with consumer awareness and knowledge towards eco-labeled food products in Malaysia. Exploratory factor analysis (EFA) was used to uncover underlying factors resulting in awareness of the existing of eco-labeled products. Four factors identify the consumer awareness towards eco-labeled food products, which are the attitude, society influence, product price and ability to perform, with 62.76 percent of total variance. In addition, the results of logistic regression model suggest that consumers who have higher income and educational level, and younger in age are more aware of eco-labeled food products and they are more likely to have a higher intention towards consuming the products. Thus food producers required to pay closer attention to the changes in consumer’s needs and demands, and develop appropriate marketing strategies that addressed the changing trends.